Prawdopodobieństwo warunkowe realizacji europejskiej opcji kupna - Stolorz, Beata (Conditional probability of exercise of European call option, 2006)
The purpose of the paper is to find out how high is a risk of investing the money in the stock options. The measurement of such a risk is function, that determines probability of exercising of call option. This function is the conditional probability determined for any price distribution of the underlying instrument. Family of these functions has a limit. Some properties of this limit are independent from this distribution. In the paper it’s been presented examples of families of functions for uniform and log-normal distribution.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 524-531